2021
DOI: 10.1177/26350106211051297
|View full text |Cite
|
Sign up to set email alerts
|

Who Needs Diabetes Education? A Qualitative Analysis of Emerging Adults With Type 1 Diabetes

Abstract: Background The purpose of this study is to explore the diabetes self-management education (DSME) needs of emerging adults with type 1 diabetes mellitus (T1DM) because addressing these needs may facilitate optimal glycemic management during this challenging transitional period. Methods A hybrid qualitative design was utilized. Emerging adults and parents of emerging adults were recruited from endocrinology and primary care clinics and through a Utah-specific T1DM online community. Interviews were conducted to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…22 Emerging adults who receive diabetes self-management education services desire integration of real-world problem-solving to diabetes barriers that may present. 23 Additionally, peer support via online media is often a preferred way to receive resources. 24,25 The T1D Financial Toolkit is a simple resource that diabetes care and education specialists can utilize to prompt discussions about relevant health insurance and financial challenges emerging adults might face and strategize solutions.…”
Section: Discussionmentioning
confidence: 99%
“…22 Emerging adults who receive diabetes self-management education services desire integration of real-world problem-solving to diabetes barriers that may present. 23 Additionally, peer support via online media is often a preferred way to receive resources. 24,25 The T1D Financial Toolkit is a simple resource that diabetes care and education specialists can utilize to prompt discussions about relevant health insurance and financial challenges emerging adults might face and strategize solutions.…”
Section: Discussionmentioning
confidence: 99%
“…MAXQDA (V.22.1.1) was used to conduct thematic analysis across transcripts as follows: a qualitative codebook with a priori deductive codes was developed using the interview guide and preliminary themes based on literature review,14–29 and inductive codes were developed during transcript review and analyst discussion. Each transcript was independently coded in its original language by three coders who were fluent in the language in which the interview was conducted.…”
Section: Methodsmentioning
confidence: 99%
“…4 10 To equitably address the complex and evolving needs of diabetes care in the pandemic and post-pandemic eras, research must adequately capture the context of care among patients and health systems in communities that are disparately affected by these challenges and yet often underrepresented in research. 13 Prior research has found that social determinants of health, such as financial factors, access to healthcare and psychosocial support have substantial impacts on patients' experience with and outcomes of diabetes care [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] and that these experiences can differ across other, intersecting factors, 19 such as race, ethnicity, language and rurality. However, few of these prior studies were conducted during or after the pandemic's onset, with most recent studies examining the experiences of patients living outside the USA during that time.…”
Section: Open Accessmentioning
confidence: 99%
See 2 more Smart Citations